BnLPAT2 gene regulates oil accumulation in Brassica napus by modulating linoleic and linolenic acid levels in seeds - Luyao Huang; Zhiqiang Liao; Yujing Zou; Yong Liu; Huihui Wang; Leping Zou; Sun Liang; Shan Tong; Yu Kang; Tuo Chen; Xinghua Xiong; Man Xing (PLoS ONE, 2025)
Lysophosphatidate acyltransferase (LPAT) catalyzes the conversion of lysophosphatidic acid to phosphatidic acid, a key step in lipid biosynthesis. This study cloned four LPAT2 genes from Brassica napus: BnLPAT2-A04, A07, A09, and C08. Functional analysis using bioinformatics, qRT-PCR (Quantitative Reverse Transcription Polymerase Chain Reaction), CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 9), overexpression, and transcriptome sequencing revealed that these genes encode proteins containing the conserved PLN02380 domain. BnLPAT2-A07/A09/C08 showed strong conservation with Arabidopsis AtLPAT2. Promoter analysis revealed multiple cis-elements related to stress, light, and phytohormone responses, with the BnLPAT2-A09/C08 promoters containing the most diverse cis-elements. Expression analysis showed that BnLPAT2-A07/C08 was highly expressed in various tissues, with BnLPAT2-A07 peaking during seed development. Overexpression of these genes increased seed oil content and the proportion of C18:2/C18:3 fatty acids, with BnLPAT2-A07 achieving an increase in oil content ranging from 4.46% to 6.44%. Gene knockout reduced oil content by 7.5% and affected fatty acid accumulation. Transcriptome sequencing analysis suggested that the BnLPAT2 genes promote the production of long-chain fatty acids, such as Linoleic acid (C18:2) and Linolenic acid (C18:3), through biological processes, including fatty acid biosynthesis, very long-chain fatty acid biosynthesis, and very long-chain fatty acid metabolism, thereby improving seed oil content. This study provides valuable insights into lipid metabolism and offers a theoretical foundation for improving oil content and fatty acid composition in B. napus.